Late holocene beach ridge sequences in northern Peru: did they register the strongest Paleo-El Niños? - Ortlieb, Luc (1989)
Along the northwestern coast of Perú, a few sequences of Holocene beach ridges have recently attracted the interest of several investigators. These costal features have been interpreted, first as evidence for tectonic and/or seismo-tectonic repeated events, and more recently as the result of paleo-El Niño phenomena. Most of the previous studies have been conducted in close relationship with archeological research programs, and a large proportion of the available radiocarbon data on the Peruvian beach ridges was provided by anthropic remains (charcoals and midden shells) collected on top of the ridges. Therefore these data do not yield ages of the edification of the ridges. A re-examination of the previous studies and a new investigation on the sequence located at Colán have been undertaken in 1988. The main objective is to determine whether the ridges have been formed during the strongest past El Niños. If the beach ridges did record paleo-El Niño conditions, a precise dating of each ridge would contribute to an historical reconstruction of these events in the upper Holocene, once post-glacial sea-level, reached its present position.